Cardiac Troponin T release after prolonged strenuous exercise - Michielsen, E. C. H. J.; Wodzig, W. K. W. H.; van Diejien-Visser, M. P. (Sports Medicine, 2008)
Over the past 2 decades, there has been a large interest in cardiac troponin T (cTnT) elevations, which are often seen following endurance sport events. There have been many reports on this topic, although sometimes with different approaches. We reviewed the available literature on cTnT elevations after prolonged strenuous exercise and discovered profound differences in the percentage of subjects reported to have elevated cTnT concentrations. This could partly be attributed to differences in immunoassay characteristics, such as cross-reactivity with skeletal troponin T, and the use of different cut-off values used in the different studies. The elevations were transient, with levels decreasing to pre-event concentrations within 24-48 hours. This might be explained by the relatively short half-life of cTnT, or water imbalance during and after the event. The release mechanism of cTnT, as well as the long-term positive or negative effects, remains unclear. Future research should therefore be aimed at clarifying the release mechanism of cTnT. Furthermore, the benefits and the possible long-term negative aspects of prolonged exercise should be evaluated.